Role of MRI for the detection of prostate cancer - Wu, Richard C.; Lebastchi, Amir H.; Hadaschik, Boris A.; Emberton, Mark; Moore, Caroline; del Pilar Laguna Pes, Maria; Futterer, Jurgen J.; George, Arvin K. (Springer, 2021)
The use of multiparametric MRI has been hastened under expanding, novel indications for its use in the diagnostic and management pathway of men with prostate cancer. This has helped drive a large body of the literature describing its evolving role over the last decade. Despite this, prostate cancer remains the only solid organ malignancy routinely diagnosed with random sampling. Herein, we summarize the components of multiparametric MRI and interpretation, and present a critical review of the current literature supporting is use in prostate cancer detection, risk stratification, and management.
Keywords: Prostate Biopsy; Prostate Cancer; Targeted Biopsy; MRI